The F1Fo-ATPase inhibitor, IF1, is a critical regulator of energy metabolism in cancer cells. (30th April 2021) - Solaini, Giancarlo; Sgarbi, Gianluca; Baracca, Alessandra
Abstract : In the last two decades, IF1, the endogenous inhibitor of the mitochondrial F1 Fo -ATPase (ATP synthase) has assumed greater and ever greater interest since it has been found to be overexpressed in many cancers. At present, several findings indicate that IF1 is capable of playing a central role in cancer cells by promoting metabolic reprogramming, proliferation and resistance to cell death. However, the mechanism(s) at the basis of this pro-oncogenic action of IF1 remains elusive. Here, we recall the main features of the mechanism of the action of IF1 when the ATP synthase works in reverse, and discuss the experimental evidence that support its relevance in cancer cells. In particular, a clear pro-oncogenic action of IF1 is to avoid wasting of ATP when cancer cells are exposed to anoxia or near anoxia conditions, therefore favoring cell survival and tumor growth. However, more recently, various papers have described IF1 as an inhibitor of the ATP synthase when it is working physiologically (i.e. synthethizing ATP), and therefore reprogramming cell metabolism to aerobic glycolysis. In contrast, other studies excluded IF1 as an inhibitor of ATP synthase under normoxia, providing the basis for a hot debate. This review focuses on the role of IF1 as a modulator of the ATP synthase in normoxic cancer cells with the awareness that the knowledge of the molecular action of IF1 on the ATP synthase is crucial in unravelling the molecular mechanism(s) responsible for the pro-oncogenic role of IF1 in cancer and in developing related anticancer strategies.